2024
DOI: 10.1039/d3cs00991b
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral metallofullerene molecular nanomagnets

Ziqi Hu,
Shangfeng Yang

Abstract: This review summarizes the significant advances in endohedral metallofullerene-based molecular nanomagnets, with a particular emphasis on their unique structures and intriguing magnetic properties arising from such structural peculiarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 265 publications
0
4
0
Order By: Relevance
“…Such a similarity among different lanthanide metals implies a trivalent state of lanthanides (M 3+ ) in TiMN@C 84 (M = La, Ce, Pr). Moreover, in principle, this template synthesis may be used, by introducing more anisotropic Dy 3+ /Tb 3+ ion, to design single-molecule magnets with exceptionally strong ligand fields that profit from the strong lanthanide-nitrogen bonding …”
Section: Results and Discussionmentioning
confidence: 99%
“…Such a similarity among different lanthanide metals implies a trivalent state of lanthanides (M 3+ ) in TiMN@C 84 (M = La, Ce, Pr). Moreover, in principle, this template synthesis may be used, by introducing more anisotropic Dy 3+ /Tb 3+ ion, to design single-molecule magnets with exceptionally strong ligand fields that profit from the strong lanthanide-nitrogen bonding …”
Section: Results and Discussionmentioning
confidence: 99%
“…39,40 Unlike paramagnetic and spin-crossover complexes wherein paramagnetic shift and electronic spin state are intrinsically susceptible to temperature, 41,42 the strong temperature dependence of the diamagnetic Y 2 F@C 80 (CF 3 ) is remarkable since the diamagnetic term of chemical shift is temperatureindependent. This unusual thermally induced δ( 19 F) variation of Y 2 F@C 80 (CF 3 ) is likely associated with the more facile cluster rotation inside the cage at elevated temperatures, as also demonstrated by temperature-dependent 45 Sc and 13 C chemical shifts of the inner carbide cluster in Sc 2 C 2 @C 80 and Sc 2 C 2 @C 82 . 43,44 Theoretical studies were further carried out to shed light on the unique cluster structure and bonding nature of M 2 F@ C 80 (CF 3 ) (M = Gd and Y).…”
mentioning
confidence: 82%
“…The types of EMFs have been greatly extended since the advent of endohedral metal clusters when electronegative nonmetal elements are also encapsulated inside fullerene cages, as exemplified by highly stable trimetallic nitride clusterfullerene (NCF) Sc 3 N@C 80 employing an icosahedral I h (7)-C 80 cage in a −6 anionic state, which is a result of the formation of the +6 charged Sc 3 N cluster . Later it was found that apart from N 3– linking three metal ions in NCFs, carbide (C 2 2– ), , oxide (O 2– ), , and sulfide (S 2– ) , can be utilized as μ 2 -bridging ligands to form +4 charged dimetallic clusters within the interior space of fullerene cages, while cyanide (CN – ) acts as a terminal ligand coordinating to solely one metal ion. These electronegative nonmetal ligands facilitate a strong metal–nonmetal bonding interaction that induces strong uniaxial magnetic anisotropy of the rare-earth metal ions, thus rendering clusterfullerenes a promising candidate of high-performance single-molecule magnets. …”
mentioning
confidence: 99%
“…Enhanced magnetic coupling can be achieved with the mediation of a delocalized unpaired electron evoking Ln– e coupling fulfilled through either a radical bridge , or a single-electron metal–metal bond, which has been realized in dilanthanide compounds bridged by three isolated iodide anions and in the form of endohedral metallofullerenes (EMFs) such as Dy 2 @C 80 (CH 2 Ph). Besides, mediating Ln···Ln coupling via superexchange interaction through nonradical ligands (N 3– , O 2– , F – , etc.) affords indirect 4f–4f coupling. For instance, strong Dy···Dy antiferromagnetic (AF) coupling is favored in oxide clusters (Dy 2 O) inside the confined space of fullerene cages. …”
mentioning
confidence: 99%